Use of Machine Learning for Personalized Care for Persons with Disabilities: Ethical and Privacy Issues - Thelma D. Palaoag, Guillermo V. Red Jr. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Machine learning remains the future of care personalization, especially in caring for persons with disabilities. However, critical ethical and privacy challenges arise, which potentially derail the deployment of machine learning technologies. This research has explored these challenges, considered possibility of machine learning being used to resolve the challenges, and examined the policy and governance frameworks that could be used to address the problem. The study adopted a scoping review method, where a scoping review process was conducted for each of the three research questions. This approach made it possible to offer an in-depth assessment of all aspects of the research problem. The findings support the available literature by establishing that critical privacy and ethical challenges exist. These challenges fall under three main categories: the technology, practice, and data. Like any other technology, machine learning is vulnerable to malicious activity and its use could breach patient privacy. Since it involves handling patient data, there is a possibility that the handling of the data itself poses privacy and ethical risks.